2020
DOI: 10.1002/clc.23514
|View full text |Cite
|
Sign up to set email alerts
|

Benefit and risk of adding rivaroxaban in patients with coronary artery disease: A systematic review and meta‐analysis

Abstract: BackgroundAlthough the European Medicines Agency and the US Food and Drug Administration have, respectively, approved rivaroxaban for the prevention of recurrent major adverse cardiovascular events in patients with myocardial infarction and stable coronary artery disease, its efficacy and safety is unclear. This meta‐analysis aimed to evaluate the benefit and risk of adding rivaroxaban in coronary artery disease (CAD) patients, focusing on treatment effects stratified by different baseline clinical presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…In the systematic review and meta-analysis on the use of rivaroxaban in coronary artery disease, it was concluded that patient's characteristics of ischemic and bleeding risk are critical in deciding about the addition of rivaroxaban [ 40 ]. The low-dose rivaroxaban in peripheral arterial disease was studied in the systematic review of randomized trials, and it was found to be effective in preventing cardiovascular events with a possible increase risk of bleeding [ 41 ].…”
Section: Role In Peripheral Artery Disease and Chronic Coronary Armentioning
confidence: 99%
See 1 more Smart Citation
“…In the systematic review and meta-analysis on the use of rivaroxaban in coronary artery disease, it was concluded that patient's characteristics of ischemic and bleeding risk are critical in deciding about the addition of rivaroxaban [ 40 ]. The low-dose rivaroxaban in peripheral arterial disease was studied in the systematic review of randomized trials, and it was found to be effective in preventing cardiovascular events with a possible increase risk of bleeding [ 41 ].…”
Section: Role In Peripheral Artery Disease and Chronic Coronary Armentioning
confidence: 99%
“…Therapeutic dose of rivaroxaban was studied in SELECT-D (Anticoagulation Therapy in Selected Cancer Patients at Risk of Recurrence of Venous Thromboembolism), a randomized, multicenter pilot trial, and was compared to the therapeutic dose of dalteparin in patients with active cancer and diagnosis of VTE. There was less cumulative VTE recurrence in the rivaroxaban group compared to the dalteparin group [ 40 ]. Based on this trial, it was concluded that rivaroxaban at standard DVT/PE dosage could be considered in patients with active cancer and diagnosis of VTE after shared decision making.…”
Section: Role In Treatment Of Venous Thromboembolism With Cancermentioning
confidence: 99%
“…Одним из недавних ярких достижений кардиологии стало обоснование нового подхода к антитромботической терапии, при котором АСК сочетают с низкими дозами ингибитора фактора Ха -ривароксабана. Высокий терапевтический потенциал этой комбинации доказан в крупных исследованиях [4][5][6] и уже отражен в международных и отечественных рекомендациях [1,2].…”
Section: ключевые словаunclassified
“…It is also often used for the prevention and treatment of thromboembolic disorders such as deep vein thrombosis, pulmonary embolism, peripheral artery disease (Bauersachs et al, 2020; Bonaca et al, 2020; Cohen et al, 2020; Schastlivtsev et al, 2019; Simmons et al, 2018; Wang et al, 2021). Therapeutic drug monitoring is critical to decrease the incidence rate of bleeding and thrombosis for personalized treatment with rivaroxaban, especially for drug interaction treatment, patients with renal dysfunction, elderly patients, patients with cardiovascular problems, and so on (Atarashi et al, 2021; Willmann et al, 2021; Xie et al, 2021; Zhang et al, 2021). In addition, an accurate analytical method is necessary for therapeutic drug monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…. Therapeutic drug monitoring is critical to decrease the incidence rate of bleeding and thrombosis for personalized treatment with rivaroxaban, especially for drug interaction treatment, patients with renal dysfunction, elderly patients, patients with cardiovascular problems, and so on (Atarashi et al, 2021;Willmann et al, 2021;Xie et al, 2021;Zhang et al, 2021). In addition, an accurate analytical method is necessary for therapeutic drug monitoring.…”
mentioning
confidence: 99%